2006
DOI: 10.1002/eji.200535803
|View full text |Cite
|
Sign up to set email alerts
|

TCR ligand avidity determines the modeof B‐Raf/Raf‐1/ERK activation leading to the activationof human CD4+ T cell clone

Abstract: The interactions between peptide/MHC complexes and their cognate TCR are essential for various T cell responses. However, the relationship between the avidity of TCR ligand and the subsequent intracellular signaling through the TCR is still unclear. To investigate the effects of TCR ligand avidity on TCR-mediated signaling, we established L cells expressing HLA-DR4 molecules covalently linked with agonistic peptide (highaffinity ligand) or altered peptide ligand (APL; low-affinity ligand) at various densities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 40 publications
1
15
0
Order By: Relevance
“…Previously we reported that B-Raf activation is regulated by Ras and mediates sustained ERK activation and subsequent IL-2 production upon TCR stimulation in human T cells [22,24]. In addition, enforced expression of B-Raf in mouse CD4 + T cells resulted in augmentation of their proliferation and prevention of anergy induction [25].…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations
“…Previously we reported that B-Raf activation is regulated by Ras and mediates sustained ERK activation and subsequent IL-2 production upon TCR stimulation in human T cells [22,24]. In addition, enforced expression of B-Raf in mouse CD4 + T cells resulted in augmentation of their proliferation and prevention of anergy induction [25].…”
Section: Introductionmentioning
confidence: 92%
“…1D). These results could be attributed to the lower activation threshold of B-Raf than Raf-1 in response to TCR stimulation [22]. The findings of TCR stimulationinducible B-Raf activation prompted us to hypothesize that B-Raf could play a role in TCR-mediated T cell responses in thymocytes.…”
Section: Expression and Activation Of B-raf In Thymocytesmentioning
confidence: 99%
See 2 more Smart Citations
“…As in other cell types, the duration of Erk signaling plays a decisive role in multiple T cell outcomes: positive versus negative selection of thymocytes (1,2), CD4 versus CD8 lineage commitment (3), response to low-affinity versus high-affinity Ags in mature T cells (4), or Th1 versus Th2 differentiation of effector T cells (5). These developmental or differentiation processes are initiated by signaling through the TCR (6,7).…”
mentioning
confidence: 99%